Surgical site infection surveillance: a Scottish perspective (2003–2010). Issue 1 (January 2013) - Sullivan, Christopher; McNeish, Jane; Mullings, Abigail; Reilly, Jacqui
Health Protection Scotland facilitates national surveillance of surgical site infection (SSI) in Scotland with all hospitals participating in the SSI programme. For the period January 2003 to December 2010, there were 1883 inpatient SSIs, resulting from 192, 007 procedures in the selected surgical categories. The inpatient SSI incidence density rates in Scotland over the duration of the SSI surveillance programme (2003–2010) showed a reduction over the eight years of surveillance for all procedures, with a significant reduction in caesarean section, hip arthroplasty, knee arthroplasty, and open reduction of long bone fracture. For all procedures, the highest proportion of SSIs detected were superficial. Data from Scotland includes information on infections occurring post-discharge from hospitals, which is an increasingly important aspect of monitoring, as length of stay in hospital is reducing over time. The introduction of readmission surveillance until day 30 post-operatively for hip arthroplasty in 2007 and post-discharge surveillance (PDS) to day 10 for caesarean section in 2009 has resulted in a higher proportion of SSIs being detected following discharge from hospital.